Domains of religious coping behavior among African Christians in NSW Australia: An exploratory qualitative study - Counted, Victor (Journal of spirituality in mental health, 2019)
This study examines the domains of religious coping strategies among African Christians in New South Wales, Australia, and the role they play in negotiating quality of life and life stressors. Study themes were drawn from interview transcripts that showed positive and negative aspects of religious coping, involving multiple domains including personal, social, and environmental attributes. Of particular interest were the correlations that respondents drew between their personal biographies, environmental stressors, human-based coping, and religious coping behavior. These results position religious coping as a social cognitive model which may arise from relationship problems, while serving the need for autonomy. Implications are discussed.